Potential pitfalls of reproductive direct-to-consumer testing - Frank Z. Stanczyk, Ph.D; Rachel S. Mandelbaum, M.D; Rogerio A. Lobo, M.D (Elsevier, 2022)
The availability of direct-to-consumer (DTC) testing has dramatically increased over the past 2 decades, particularly those targeted at reproduction and fertility. Several ethical concerns exist with regard to DTC tests, including the lack of governmental regulation and consumer protection, standardized laboratory methodology, and clinical validity and actionability. Physicians must familiarize themselves with the pitfalls of DTC tests to best aid patients in interpreting DTC test results and guide them toward evidence-based treatment plans.